What is a processing speed weakness? Importance of cognitive ability when defining processing speed in a child psychiatric population. Issue 2 (17th February 2022) - Forchelli, G. A.; Vuijk, P. J.; Colvin, M. K.; Ward, A. K.; Koven, M. R.; Dews, A.; Doyle, A. E.; Braaten, E. B.
ABSTRACT: There is growing evidence that processing speed (PS) deficits in youth with neuropsychiatric conditions are associated with functional difficulties. However, there is no consistent definition of slower PS; specifically, whether slower PS should be defined as a discrepancy from same-aged peers (normative weakness) or as an intrapersonal deficit relative to overall cognitive ability (relative weakness). In a sample of clinically-referred youth, we calculated slower PS both ways and examined the impact on adaptive, academic, and psychopathology outcomes in relation to different levels of cognitive ability. Significant PS x cognitive ability interactions were found on adaptive and academic outcomes. A norm-based weakness in PS (PSI Standard Score <85) was associated with lower adaptive skills and lower academic skills regardless of cognitive ability. In the above average cognitive ability group, relatively lower PS (PSI > 15 point difference from VCI) was associated with significantly lower academic performance. No significant associations were found for general psychopathology. Results suggest a normative weakness in PS impacts functional outcomes interactively and differently with level of general cognitive ability. Data suggest that higher cognitive ability may be somewhat protective from the impact of normatively weak PS on adaptive outcomes; however, youth across all abilities with normatively weak PS showed weaker academic performance. Second, children with high cognitive abilities and relatively weak PS showed discrepant performance compared to comparison group. Implications and areas for future research are discussed.